Rancang Bangun Website Majelis Jemaat GKE Bumi Palangka (MJBP) PHP dan MySQL - Permatasari, Lany Aprilia; Oktaviyani, Enny Dwi; Christina, Sherly (Universitas Palangka Raya, 2021)
GKE Bumi Palangka Congregation Council is the leader of the Church Congregation in Palangka Raya which houses four churches, of course, has a large accumulation of congregations. One of the duties and jobs of the GKE Bumi Palangka Congregational Daily Working Body (BPH MJBP) is to regulate the stewardship of the Church and to collect data on the congregation every year. The problems that exist in the Bumi Palangka GKE Congregational Assembly are the Jamaat's service system and the data has not been computerized and integrated and the lack of media to share or disseminate information that is in the Bumi Palangka GKE Congregational Assembly. In designing the website of the GKE Bumi Palangka Congregational Assembly, themethod is used waterfall with stages, Requirements Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing, Operation and Maintenance. The software used in building this website is Visual Studio Code, MySQL, and XAMPP. This website has been tested with blackbox testing which results in that the features on the website can run well. This MJBP Website Design was developed with the aim of planning, supervising, directing and delegating work to all service departments that have a relationship or coordination. As well as managing computerized church and congregation data so as to produce congregation information such as recapitulation reports